2017
DOI: 10.1016/j.biopha.2017.09.137
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment with chaethomellic acid A reduces glomerulosclerosis and arteriolosclerosis in a rat model of chronic kidney disease

Abstract: The high prevalence of end-stage renal disease emphasizes the failure to provide therapies to effectively prevent and/or reverse renal fibrosis. Therefore, the aim of this study was to evaluate the effect of long-term treatment with chaethomellic acid A (CAA), which selectively blocks Ha-Ras farnesylation, on renal mass reduction-induced renal fibrosis. Male Wistar rats were sham-operated (SO) or subjected to 5/6 renal mass reduction (RMR). One week after surgery, rats were placed in four experimental groups: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The administration routes that require less manipulation techniques are recommended [68]. In animal experimentation, several routes for substance administration are currently available, namely enteral (through the digestive tract), either oral (into the mouth) or gavage (esophageal, gastric, nasogastric or orogastric), intravenous (into a blood vessel), epicutaneous (onto the skin), intradermal (into the skin), subcutaneous (under the skin), transdermal (across the skin), intramuscular (into a muscle), transcorneal (onto the eye), intraocular (into the eye), intracerebral (into the brain), epidural (into the dura mater surrounding space), intrathecal (into distal spinal cord surrounding space), intraperitoneal (into the peritoneal cavity), intraosseous (into the marrow cavity), intranasal (sprayed into the nose and then absorbed by the nasal mucous membranes or into the lungs), intratracheal (into the lungs by direct tracheal instillation), inhalation, and other less common techniques, such as those using other body natural orifices, surgical exposure, and others regarding species-specific anatomic features [68,69,70,71,72].…”
Section: Administration Routesmentioning
confidence: 99%
“…The administration routes that require less manipulation techniques are recommended [68]. In animal experimentation, several routes for substance administration are currently available, namely enteral (through the digestive tract), either oral (into the mouth) or gavage (esophageal, gastric, nasogastric or orogastric), intravenous (into a blood vessel), epicutaneous (onto the skin), intradermal (into the skin), subcutaneous (under the skin), transdermal (across the skin), intramuscular (into a muscle), transcorneal (onto the eye), intraocular (into the eye), intracerebral (into the brain), epidural (into the dura mater surrounding space), intrathecal (into distal spinal cord surrounding space), intraperitoneal (into the peritoneal cavity), intraosseous (into the marrow cavity), intranasal (sprayed into the nose and then absorbed by the nasal mucous membranes or into the lungs), intratracheal (into the lungs by direct tracheal instillation), inhalation, and other less common techniques, such as those using other body natural orifices, surgical exposure, and others regarding species-specific anatomic features [68,69,70,71,72].…”
Section: Administration Routesmentioning
confidence: 99%
“…The former was to examine the general changes of pathomorphology, which was expressed as histopathological scores according to the description of Nogueira et al. (2017). The latter was to evaluate the degree of collagen deposition, which was expressed as collagen area’s ratio according to our description (Wang et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…To observe the histological changes of kidney, the partial renal tissues were fixed in 4% of formaldehyde solution and embedded in paraffin for hematoxylin and eosin (HE) staining and Van Gieson (VG) staining. The former was to examine the general changes of pathomorphology, which was expressed as histopathological scores according to the description of Nogueira et al (2017). The latter was to evaluate the degree of collagen deposition, which was expressed as collagen area's ratio according to our description (Wang et al, 2019).…”
Section: Histological Analysismentioning
confidence: 99%
“…In the experimental model of 5/6 renal mass reduction [RMR] in rats, long-term administration of chaetomellic acid decreased the oxidative stress in kidneys [ 126 ]. Using the same RMR model, the same authors found a decrease in glomerulosclerosis and arteriolosclerosis after chaetomellic acid administration [ 127 ].…”
Section: Potential Therapeutic Approaches Targeting the Ras Pathwaymentioning
confidence: 99%